Design Briefs for Industrial Design Studio Courses: Determination of Expectations and Requirements - Duysal Demirbaş; Şebnem Timur Öğüt (Anı Publishing, 2018)
This study aims to determine the basic elements relating to a tool to be used in Design Studio courses; one of which intertwined with daily life technologies through the usage of patterns and habits of a Design Brief. In order to address the main purpose of the study in a holistic approach, a mixed method research was used combining qualitative and quantitative methods. Data were collected through face-to-face interviews and online survey forms from Design Studio course instructors working in industrial design departments in Turkey. The study presents there is a need to reconstruct some components of the Design Brief in such a way to accompany the dynamic structure of the project process, there are problems related to the current medium, and the attitudes of the new generation students must be taken into consideration when designing a new medium for the Design Brief as a new learning tool.